2021
DOI: 10.1177/23197145211059268
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effectiveness of Received Offline Word of Mouth: Role of Acquired and Ascribed Homophily

Abstract: This research examines how similarities in educational and ethnic backgrounds (status homophily), between word of mouth (WOM) participants, influences the effectiveness of received offline WOM on the recipient’s behavioural intentions. The educational similarity between individuals is conceptualized as acquired homophily, whereas ethnic similarity is defined as ascribed homophily. This study employs scenario-based experiments, and the results suggest that positive and negative WOM received from homophilous sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…Depending on the specified link, proximity or intimacy between a sender and a receiver, the recipient can rely on the recommendations made by WOM sources regarding specific services. This is supported by Chawdhary and Weber (2021) who revealed that recommendations from WOM sources with similar values to the WOM receiver are more effective in influencing the WOM receiver's decision-making process than recommendations from sources with dissimilar values. This perceived similarity between homophily and dissimilar individuals stems from the logic of homophily, or the love of people who are identical in some ways.…”
Section: Perceptual Homophily Between Public Buyers and Sme Suppliers...mentioning
confidence: 79%
See 1 more Smart Citation
“…Depending on the specified link, proximity or intimacy between a sender and a receiver, the recipient can rely on the recommendations made by WOM sources regarding specific services. This is supported by Chawdhary and Weber (2021) who revealed that recommendations from WOM sources with similar values to the WOM receiver are more effective in influencing the WOM receiver's decision-making process than recommendations from sources with dissimilar values. This perceived similarity between homophily and dissimilar individuals stems from the logic of homophily, or the love of people who are identical in some ways.…”
Section: Perceptual Homophily Between Public Buyers and Sme Suppliers...mentioning
confidence: 79%
“…Currently, literature has associated homophily with the effectiveness of WOM (Amani, 2022a). This link suggests that a strong connection between sender and recipient may have a beneficial effect on WMMD (Amani, 2022a; Chawdhary and Weber, 2021). Depending on the specified link, proximity or intimacy between a sender and a receiver, the recipient can rely on the recommendations made by WOM sources regarding specific services.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…and tend to behave similarly and promote similar behaviours (Chawdhary & Dall'Olmo Riley, 2015). It is assumed that homophily influences the strength of social ties and trust between communicators (Chawdhary & Weber, 2021;Leonhardt, Pezzuti & Namkoong, 2020). Therefore, eWOM on SNSs is more likely to take place between individuals where the information flow is frequent and impactful (Leonhardt, Pezzuti & Namkoong, 2020).…”
Section: 3electronic Word Of Mouth and Social Relationship Variablesmentioning
confidence: 99%